The relationship between exercise and Physical Fitness towards Economic Survival: A Comparative Study of Gender discrimination - Kuo Yen-Ku; Ahmad El Askary; Rumi iqbal doewes; Basem H. Elesawy; Wang, Jiun-Hao; MD Shamim Hossain (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Everyone's health is critically important. Managing health problems is just as critical as surviving economically. Any country's economic survival is entirely contingent upon its economic strategy. The study of the relationship between exercise and fitness and its impact on economic survival has as its primary objective educating us about the significance and necessity of exercise and physical fitness in our lives. Exercise and physical activity have unquestionable health benefits. The comparative study of differences in physical fitness and activity between men and women. The study's independent variables include exercise and physical fitness, while the dependent variable is economic survival. The data analysis was performed using AMOS 26v. Because this study contained three hypothesis statements, the results suggested a positive and significant link between the variables.